Pelatihan Business Model Canvas sebagai Strategi Peningkatan Kompetensi Perencanaan Bisnis Siswa SMKN 6 Padang - Dessyta Gumanti; Reni Respita; Widya Astuti; Detman; Caterina Lo; Serli Diovani Teza (Kilau Publishing, 2026)
Entrepreneurship education is very important in building the economic independence of the younger generation. Unfortunately, many vocational high school students in Indonesia do not yet have practical knowledge about good business planning. Therefore, this community service activity is held to enhance the entrepreneurial skills of SMKN 6 Padang students. This activity uses the Business Model Canvas (BMC) training method, which is a practical and easy-to-understand approach to business planning.Thirty students from the XI Hospitality Department participated in this activity. The methods used were very varied, ranging from lectures, workshops, group discussions, to group simulations of creating a BMC. As a result, the participants had a better understanding of the nine elements of the BMC, namely customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. They also successfully created BMCs for their respective business ideas.This program proves that BMC-based training is very effective in fostering the entrepreneurial spirit of vocational students. Therefore, this program is highly recommended as a model for sustainable service in higher education outreach programs. Thus, it is expected to help improve the economic independence of the younger generation in Indonesia.